MARKET TRANSACTION MODEL OF "CANDAK KULAK" IN EMPOWERING WOMEN IN PANGGUNGDUWET RESTRICTED VILLAGE OF BLITAR DISTRICT - Nurul Farida; Hery Suprayitno (JARES (Journal of Academic Research and Sciences), 2019)
The purpose of this study is to describe the market transaction model "candak kulak" in the empowerment of women in restricted village in Panggungduwet especially those who live in rural areas. The research method uses interview, participant observation and documentation studies. Next is determination of location, building access to informants, and its implementation by collecting data, recording information, breaking content, and storing data again at the initial step. The subject of this research is the market transaction model in the form of "candak kulak" in the Panggungduwet village of Blitar Regency. Analysis that arises in restricted and underdeveloped areas, the development strategy of restricted villages in Blitar District is development in the agribusiness-based agricultural sector, because most of the population are farmers. The output of this study can provide an overview related to the market transaction model "candak kulak" in the restricted village in Panggungduwet Blitar Regency. In this effort to spur development in terms of economic and social aspects in restricted areas, the development program must prioritize three main aspects, namely alleviating poverty, improving the quality of human resources, and building infrastructure.